Enhancing Reading Comprehension through Speed Reading: A Study of Eighth-Grade Students in an Indonesian EFL Classroom - Munir, Munir; Azizah, Izmi; Haque, Nazmul (Fakultas Sastra - Universitas Muslim Indonesia, 2024)
This study investigates the impact of the Speed-Reading method on the reading comprehension of eighth-grade students at SMPN 8 Makassar. Utilizing a quantitative pre-experimental design, the research involved a one-group pretest-posttest approach, engaging 34 students. The intervention consisted of structured speed-reading sessions supplemented with visual aids, aimed at enhancing students' reading speed and comprehension. Data were collected through pre-tests and post-tests and analysed using SPSS to determine the effectiveness of the Speed-Reading method. The findings reveal a significant improvement in students' reading comprehension scores post-intervention. The mean pre-test score of 59.29 increased to 83.5 in the post-test, with statistical analysis confirming the significance of this improvement (p < 0.05). These results align with previous studies, highlighting the Speed-Reading method's efficacy in fostering a more engaging and cooperative learning environment. The method not only boosts reading speed but also enhances comprehension, making it a valuable addition to EFL instructional strategies. The study concludes that the Speed-Reading method is an effective pedagogical tool for improving reading comprehension in EFL contexts. Its implementation can lead to substantial gains in students' reading abilities, suggesting its broader applicability across various educational settings. Future research should explore the long-term benefits and potential adaptations of Speed-Reading techniques to further validate and expand upon these findings.